Stability evolution mechanisms and control strategies for lower and upper trapezoidal blocks in fully mechanized top-coal caving faces of extra-thick coal seams - Qin, Binbin; He, Fulian; Zhang, Qinghua; Zhang, Zhijun; Sun, Guoxi; Liu, Xiaohu (Frontiers in Earth Science, 2025)
In underground coal mining operations, particularly in fully mechanized top-coal caving (FMTC) faces of extra-thick coal seams, structural instability after key stratum fracturing will cause severe deformation and damage to the surrounding rock mass of the working face. The methods of field investigation, theoretical analysis, physical similarity simulation, and engineering tests were employed to investigate the instability characteristics and interaction laws of the lower and upper trapezoidal block structures in the FMTC face in extra-thick coal seams with dual key strata during periods of pressure. A mechanical model of the stability of the lower and upper trapezoidal blocks above the working face with severe and weak periodic pressures was established, and the stability transformation law, interaction relationship, and influencing factors of the stability of the lower and upper trapezoidal blocks with the dual key strata working face in the extra-thick coal seam were studied. The results show that (1) it is easy to induce the sliding instability of the lower and upper trapezoidal blocks with the advance of the working face. (2) The sliding instability coefficients of the lower and upper trapezoidal blocks are positively correlated, whereas the rotational deformation instability coefficients are negatively correlated. (3) An increase in the distance between the lower and upper key strata easily induces sliding instability in the upper trapezoidal block and sliding instability and rotational deformation instability in the lower trapezoidal block. (4) Increasing the mining height could improve the sliding stability of the lower and upper trapezoidal blocks and the rotational deformation stability of the upper trapezoidal block, but it is easy to induce rotational deformation instability of the lower trapezoidal block. (5) A higher support force on hydraulic supports improves sliding stability in lower and upper trapezoidal blocks but does not affect rotational deformation stability. Finally, the rationality and reliability of the study are verified by engineering applications in the 8309 working face of the Tongxin Coal Mine.